RANCANG BANGUN SISTEM INFORMASI PENJUALAN MENGGUNAKAN METODE WATERFALL - Candra Budi Susila Candra Budi Susila; Miftahul Huda Huda (Jurnal Qua Teknika, 2021)
Abstract - esign and Design of Computer Sales Information Systems using the waterfall method is a study that aims to design and build sales information systems at a computer retail store or "Artha Komputer Center". Artha Computer Center is one of the retails or stores in Pacitan that provides various types of computers and laptops. In the management of sales that are still conventional in nature, this research focuses more on the design and implementation of systems that hope to provide alternative solutions in the management of goods. So with this sales information system, it is expected that the management of goods is more organized, sales transactions are safer from mistakes. This waterfall method uses a sequential approach by following several phases, including system requirements analysis, system design, coding on the system, testing and the last one is maintenance..